Improving Students’ Speaking Skill Through Drama at the Eighth Grade of SMPN 9 Palopo - Marwati, Marwati (FOSTER: Journal of English Language Teaching, 2020)
This paper dealt with the effectiveness of drama techniques in enhancing student speech at SMPN 9 Palopo in 8th grade. The research was mainly sample. This investigation was carried out in two classes: experimental and control classes. Sixty students from VIII SMPN 9 Palopo graduates attended this research. The sample of research for the level of VIII 6 was 30 students as experimental classes, and the class of 8 / 1 was composed of 30 students. The method is voice check-in research. The students will be evaluated and assessed by this study. SPSS, 20, analyzed the data. Data were analyzed. The study results show that the use of dramatic materials can improve the skills of speakers. The calculation results show that the scores of students in the experimental class are better than the scores of students in the control class. Based on data analysis, a post-test average value of 10,5300 > 7,5700 is higher than the pre-test average. The average value in the control class is also more significant than the average preliminary value. Based on the analysis of the data, the lesson of speech using effective dramatic techniques at 9 Palopo can be concluded. It can be concluded. The results of the experimental classes can be shown that they are higher than the control class.